Loss Evaluation of Dike-Break-Induced Flood Disasters Based on Flood Evolution Simulation - LI Wenhuan; ZHI Huanle; JIANG Shuihua; LEI Sheng; HUANG He (Renmin Zhujiang)
Since the rapid economic development within the dike is inconsistent with the level of flood control management,dike break is prone to occur under over-standard floods and causes serious losses of life,economy,and ecological environments.Taking a key dike in the Poyang Lake area as an example,this paper proposed a dike-break-induced flood evolution simulation method based on hydrodynamics.The proposed method adopted the MIKE 21 software for dike-break-induced flood evolution analysis.The roughness of the underlying surface was determined reasonably according to different types of land use.Meanwhile,quantitative evaluation models of life,economic,and environmental losses that had clear physical meaning were established in the Python platform.The research results can provide references for flood warning and risk management and control of flood disasters in protected areas.